A comparative study of interface material through selective microwave hybrid heating for joining metal plates. (2022) - Rawat, Saurabh; Samyal, Rahul; Bedi, Raman; Kumar Bagha, Ashok
Abstract: The development of joints using microwave hybrid heating (MHH) received extensive attention over conventional heating due to its uniform heating, environment friendly characteristics. For effective microwave joining of bulk metals, joint region was targeted selectively naming it as selective microwave hybrid heating (SMHH). Microwave joining of stainless steel using Nickel as interface material is explored extensively through MHH; however no comparative study showing better interface material for microwave joining of Stainless steel is reported. In the present study, SS304-SS304 lap joint is simulated for two different interface materials that are nickel and Inconel-718 for an exposure time of 22 min. These joints were developed using pulverized charcoal as a susceptor material and at the power output of 700 W. Microwave hybrid heating has been simulated by implementing different assumptions and boundary conditions at better mesh quality. A time-temperature curve, resistive heating, electric field distribution, and temperature profile along different directions are those parameters that have been discussed to examine better interface material. From the results, it is observed that Inconel-718 shows better resistive heating when compared to nickel interface material, however electric field distribution remains similar for both interface materials. Further, the time-temperature profile revealed that the time taken for Inconel-718 interface material to reach fusion zone is lesser than Nickel interface material.